Nation, identity and justice: a comparative study of American and Malaysian Muslim poets, Daniel Abdal Hayy Moore and Wong Phui Nam (a.k.a. Razali Abdullah) - Abdul Manaf, Nor Faridah (IIUM Press, International Islamic University Malaysia, 2009)
Introduction: In an article on the position of the poet in society, Kenneth Rexroth argued that Plato's disfavour of poets was not early but late since criticism and rejection of poets had been going on since the time of ancient Egypt and Babylon. While the debate continues and has possibly taken a new turn to asking how effective poetry is today or how relevant poets are to modern societies, this study is keen on exploring how two poets of different nationalities but of the same faith (Islam) embrace poetry and use it to articulate their thoughts on issues relating to identity, nationhood and justice. The two poets are Daniel Abdal Hayy Moore, an Anglo-American and Wong Phui Nam, a Chinese Malaysian. Both are Muslims.